Complete geography - Simon Chapman (Oxford University Press, 1998)
Covering the Geography syllabuses for GCSE and Standard Grade, this work serves as an effective exam preparation tool. It represents an integrated approach, and offers questions. It provides case studies giving students a range of examples to use in the exam. It includes decision-making exercises